Seeing red : HIV/AIDs and public policy in Canada - Hindmarch, Suzanne; Orsini, Michael, 1967-; Gagnon, Marilou (University of Toronto Press, 2018)
Featuring the diverse experiences of people living with HIV, Seeing Red highlights various perspectives from academics, activists, and community workers who think ahead to the new and complex challenges associated with the condition.